2016
DOI: 10.1093/nar/gkw593
|View full text |Cite
|
Sign up to set email alerts
|

Identification of consensus binding sites clarifies FMRP binding determinants

Abstract: Fragile X mental retardation protein (FMRP) is a multifunctional RNA-binding protein with crucial roles in neuronal development and function. Efforts aimed at elucidating how FMRP target mRNAs are selected have produced divergent sets of target mRNA and putative FMRP-bound motifs, and a clear understanding of FMRP's binding determinants has been lacking. To clarify FMRP's binding to its target mRNAs, we produced a shared dataset of FMRP consensus binding sequences (FCBS), which were reproducibly identified in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 38 publications
(84 reference statements)
4
47
0
Order By: Relevance
“…Scanning inhibition is thought to be further increased by recruitment of RG4-stabilizing proteins 63,66 such as fragile X mental retardation protein (FMRP) 73 , which binds to many RG4-harbouring mRNAs 74,75 (FIG. 2b).…”
Section: ′ Utr Structures In Ribosome Scanningmentioning
confidence: 99%
“…Scanning inhibition is thought to be further increased by recruitment of RG4-stabilizing proteins 63,66 such as fragile X mental retardation protein (FMRP) 73 , which binds to many RG4-harbouring mRNAs 74,75 (FIG. 2b).…”
Section: ′ Utr Structures In Ribosome Scanningmentioning
confidence: 99%
“…Dramatic changes in polysome-association of these mRNAs were observed in the absence of FMRP, indicating that translational dysregulation of these mRNAs may underpin FXS 123 . Recently, this was redefined by large-scale CLIP (crosslinking immunoprecipitation) studies, where 34,218 consensus FMRP binding sites in 3,703 genes were identified 124 . It was reported that a G4 sequence in the FMR1 mRNA provides the docking site for FMRP.…”
Section: Fmrpmentioning
confidence: 99%
“…How FMRP recognizes and binds its functional targets is also not well understood. Several studies have reported transcript and RNA motif targets for FMRP in vitro and in vivo (Ascano et al, 2012;Brown et al, 2001;Darnell et al, 2001Darnell et al, , 2005aVasilyev et al, 2015), yet considerable disagreement among these studies remains about the identity of RNA sequences that interact with FMRP with high-affinity (Anderson et al, 2016). RNA G-quadruplex sequences have been repeatedly identified as binding targets of FMRP Schaeffer et al, 2001), but other studies have found that FMRP binds completely different short RNA motifs (Ray et al, 2013) while still others seem to show that FMRP displays almost no sequence specificity at all and instead binds all along the coding sequence of its target transcripts (Darnell et al, 2011).…”
Section: Introductionmentioning
confidence: 99%